Ethnic Considerations When Planning Lip Augmentation - Borg, Tiffanie-Marie; Mackay, Jennifer (Facial Plastic Surgery, 2024)
Ideal standards of beauty including preferred lip characteristics vary between ethnicities. Although plump, well-defined lips are globally associated with youth, variation exists with regard to the perceived ideal lip volume and proportions between ethnicities. Proportions that may be assessed when planning lip augmentation include the upper-to-lower lip ratio, philtrum length, upper and lower vermilion heights, the ratio between the philtrum height and that of the upper vermilion, and the lip height-to-lip width ratio.It is important that accurate assessments of patients are made pre- and postaugmentation. However, many aesthetic assessment tools are based on Caucasian models with limited use in other ethnicities. We present a review of the ideal lip characteristics and assessment techniques accounting for ethnicity, with a view to providing practitioners an evidence-based approach to lip assessment and treatment planning for patients of all backgrounds.
Keywords: lip aesthetics; lip proportions; lip augmentation